Poverty and inequality: economic growth is better than its reputation - Angelsen, A.; Wunder, Sven (Fagbokforlaget, 2006)
This chapter first clarifies the definitions of the three key words in its title--poverty, inequality and economic growth. In particular, the evolution of the concept of poverty is discussed followed by a section on the mechanical and empirical links between income poverty, inequality and growth. The concept of "pro-poor growth" is introduced thereafter and defined as growth which raises the income relatively more for the poor than the better-off groups, i.e., growth with improvements in the income distribution. The authors argue that the prospects for pro-poor growth depend both on the initial conditions and on the type of growth, i.e., in which sectors growth occurs and its degree of labour intensity.